Accepting, active and in control: older women's experiences of ageing with peripheral arterial disease. Issue 12 (16th July 2018) - Bassett, Kimberley; Gullifer, Judith; Varcoe, Ramon L.
Abstract: The population of Australia is ageing, with women being the primary beneficiaries of this increase in longevity. Increasingly older individuals are being diagnosed with different chronic illnesses such as peripheral arterial disease (PAD) which causes blockages of the blood vessels in the legs resulting in pain, non-healing ulcers, immobility and the potential amputation of the threatened limb. PAD has been traditionally thought to affect men more than women. Resultingly, women have been under-represented in clinical trials of PAD and under-diagnosed in the health-care setting. However, it has recently been acknowledged that women are indeed more likely to suffer from PAD than men due to increased presence of disease and survival advantage. As such, very little is known about women's understanding of and the meaning they create of their experiences of PAD. Therefore, how older women with PAD experience the ageing process is the focus of this qualitative research project. Interviews were conducted with 11 women from Sydney, Australia aged over 65 years who had been diagnosed with PAD. The interviews were analysed using an inductive thematic analysis. Three manifest themes were constructed: independence and control, active and involved, and the acceptance of ageing. These findings emphasised the idea that despite the presence of a chronic illness and increased age, remaining independent and engaged with life was vital to these women's wellbeing. Their subjective experiences of ageing reflect the fact that by adapting to the physical, mental and social changes that come with growing older, the focus does not need to be on loss and decline but rather can be about the continuation of life that can be both positive and meaningful.